Rethinking critically and holistically: literary scholarship on Mary Anne Sadlier and the female Irish immigrant experience - M., Alashjaai Nouf Fahad; Bahar, Ida Baizura (PalArch, 2020)
This paper focuses on the life of the Irish author Mary Anne Sadlier (1820-1903) who wrote under the pseudonym of J. Sadlier. Her novels are set against the backdrop of The Great Famine (1845-1849) and depict the lives of Irish female migrants of the 19thcentury. In thispaper, we offer a critical and holistic academic review of Sadlier’slife and literary scholarshipon her works of fiction with regards to the experience of female Irish immigrants during the harsh and extremely challenging period in Irish history of the Great Famine also known as the Irish Potato Famine.